THE EFFECTIVENESS OF DIGITAL PROJECT-BASED LEARNING MODEL ON STUDENTS' ENGLISH ACADEMIC VOCABULARY COMPETENCE - Arimuliani Ahmad; Estika Satriani; Fauzul Etfita; Affidah Binti Morni; Yulianto Yulianto (JEE (Journal of English Education), 2026)
Enhancing academic vocabulary is an essential element in studying the English language because it is fundamental for academic literacy and professional communication. Since it is crucial, many students experience obstacles in determining it fluently because traditional teaching methods focus on memorization rather than on using it in a meaningful way. This research aim to determine the significant effect of using digital project-based learning on students' academic vocabulary competence. A quasi-experimental design was implemented by a one-group pre-test and post-test. There were thirty undergraduate students from the English Language Education Department. Data were gathered by an academic vocabulary test and analyzed by using descriptive statistics and a paired-sample t-test. The results showed that digital project-based learning has a significant effect on students’ English academic vocabulary competence, with a significance value of 0.000 (p < 0.05). This finding proved that digital project-based learning is an effective model for enhancing students’ English academic vocabulary in higher education.